PEMBANGUNAN POLITIK PENDIDIKAN MENUJU MASYARAKAT BERMARTABAT - Ritaudin, M. Sidi (Universitas Islam Negeri Raden Intan Lampung, 2014)
THE DEVELOPMENT OF POLITICS OF EDUCATION TOWARD A DIGNIFIED SOCIETY: The development of politics of education is currently faced with the development of science and technology in the communication revolution that gave birth to the global era. The globalization challenge begins when all nations strive to perform ahead of the competition through a reorientation of thought and reconstruction of the institutional system. This paper assumes that Islam is potential to be an independent variable in giving meaning and values to reach a qualified and dignified education. If it is not offset by the enforcement of religious values in the education system and curriculum, the progress of science, instead of bringing the community with dignity, can even lead to the destruction of mankind. As a pluralist state, Indonesia is also faced with the demands of unity in cultural diversity. To that end, efforts must be taken to maximize multicultural education by entering a multicultural subject into the curriculum at all levels.